SEX EDUCATION PERSPEKTIF AL-QUR’AN TINJAUAN HERMENEUTIS MA’NA CUM MAGHZA QS. AN-NUR: 30-31 - Faridatun Nisa; Isarotul Imamah; Ahmad Fahrur Rozi; M Safwan Mabrur (UIN Siber Syekh Nurjati Cirebon, 2022)
Based on the fact that there are many sexual deviations nowadays, this paper tries to describe sexual education in Islam, starting from QS. al-Nur: 30-31. The interpretation of the two verses, if viewed only from the perspective of the nakedness, cannot fully contain the significance or the main message, so that further studies are needed with an analysis of contemporary interpretations to find the main message and contextualize it at the present time. As a result, the two verses have the main message to guard and maintain any gaps or opportunities that will lead to badness and crime, with the main word farj which is always juxtaposed with the words ahfaza and ahsana, meaning to guard and maintain. Which gap or opportunity is also included in the realm of sexual relations. The message of care is included in the value of safety and justice that applies to both women and men. This study is expected to be able to answer the problem of sexual deviation that often occurs recently. The author uses a hermeneutical ma'na cum maghza approach to examine the two verses. This paper uses a ma'na cum maghza hermeneutical approach to examine these two verses. As a result, the two verses have the main message to guard and maintain any gaps or opportunities that will lead to badness and crime, with the main word farj which is always juxtaposed with the words ahfaza and ahsana, meaning to guard and maintain. Which gap or opportunity is also included in the realm of sexual relations. The message of care is included in the value of safety and justice that applies to both women and men. This study is expected to be able to answer the problem of sexual deviation that often occurs in recent times.Pembahasan mengenai seksualitas masih ramai dikaji dari berbagai segi bidang keilmuan. Terutama mengenai pendidikan seksual. Sayangnya, yang memperhatikan pendidikan seksual mayoritas adalah peneliti, civitas akademika. Orang tua yang masih mempertahankan adat nenek moyang tidak memiliki kesadaran akan pentingnya pendidikan seksual bagi anak-anak mereka. Mereka bahkan menganggap pembahasan yang terkait dengan seksualitas adalah suatu hal yang tabu. Hal itulah yang menjadi salah satu penyebab masih maraknya penyimpangan seksual. Berdasar pada suatu kenyataan mengenai banyaknya penyimpangan seksual pada masa kini, tulisan ini mencoba menjabarkan pendidikan seksual dalam Islam, berangkat dari QS. al-Nur: 30-31. Tulisan ini menggunakan pendekatan hermeneutis ma’na cum maghza untuk mengkaji kedua ayat tersebut. Hasilnya, kedua ayat tersebut memiliki pesan utama untuk menjaga dan memelihara segala celah atau kesempatan yang akan membawa pada keburukan dan tindak kejahatan, dengan kata utamanya farj yang selalu disandingkan dengan kata ahfaza dan ahsana, artinya menjaga dan memelihara. Yang mana celah atau kesempatan tersebut juga masuk dalam ranah hubungan seksual. Pesan penjagaan tersebut masuk ke dalam nilai keselamatan dan juga keadilan yang berlaku bagi perempuan maupun laki-laki. Kajian ini diharapkan dapat menjawab problem penyimpangan seksual yang sering terjadi belakangan ini.